DETERMINATION OF REDUCED SULPHUR SPECIES IN SEDIMENTS–AN EVALUATION AND MODIFIED TECHNIQUE - Duan W.M.; Coleman M.L.; Pye K. (My University, 1997)
Previous studies have indicated that the separation and quantification of different species of reduced sulphur in sediments have suffered from uncertainty in selectivity and recovery of the acid volatile sulphur pool and pyrite sulphur pool. This has probably resulted in either overestimation or underestimation of the sedimentary sulphur pools. This could be caused by differences in reagents and conditions of the analysis and by improper in situ sample pre-treatment, but the major problem is caused by the diversity of standard materials which were used and the discrepancy with real samples in natural systems. The effects of SnCl2, ZnAc and heat on digestion recovery have been investigated using anaerobic sediments and sulphide-rich concretions from a modern salt marsh environment in north Norfolk, UK. Acid volatile sulphur (AVS) and more refractory sulphide phases, termed pyrite sulphur (PS) here, are the major forms of reduced sulphur, but elemental sulphur (ES) is also significant. We found that AVS would be mostly transferred to the ES pool as a result of oxidation without in situ ZnAc treatment, and ES would be recovered in a hot Cr distillation step if not extracted before AVS and Cr extractions. A three-step sequential digestion procedure, after prior elemental S extraction, on ZnAc-treated samples was used to distinguish these different reduced species. Modifications have also been made to the process of distillation and collection of released H2S in order to retrieve enough precipitated S for later isotopic analysis. Pyrite sulphur, as defined by this extraction scheme, is divided into a less mature fraction, as distilled by cold Cr reduction, and a mature fraction, by hot Cr reduction. This method could be used as an index of the degree of the maturity of iron sulphide phases in recent sedimentary environments.
Keywords: SEDIMENTARY SULPHIDES; ANALYTICAL METHODS; PYRITE; AVS; ELEMENTAL S